Peripheral Neutrophil-to-Lymphocyte Ratio (NLR) and Breast Cancer Distant Metastasis: Analysis of a Simple Diagnostic Biomarker - Ni Putu Yenny Kendarini (Journal of Global Pharma Technology, 2020)
Introduction: Neutrophils and lymphocytes serve as easily accessible indicators representing the immune landscape in breast cancer. Combination of such variables in the form of neutrophil-to-lymphocyte ratio (NLR) allowed for extensive analysis and better interpretation. The heterogeneity in predictive role of NLR to prognosticate breast cancer sruvivalcould be attributed to metastatic spread. Methods: Data from breast cancer patients attending Oncology clinic in Sanglah Hospital, Bali was collected retrospectively. Samples were selected by simple random sampling technique from a sampling frame of patients with available preoperative complete blood count in the registry. Bivariate and multivariate analysis was performed with NLR value stratification using optimal NLR cut-off value derived from receiver operating characteristic (ROC) curve analysis. Results: A total of 51 patients diagnosed within the period of January 2016 through November 2017 were investigated. The cut-off point of NLR value in this study was 3.1 (Area under ROC curve [AUC]: 0.826). A significant association between NLR value and distant metastasis was found consistentlyin bivariate (PR 5.4, 95%CI 2.5-11.8, p=0.001) and multivariate analysis (Adjusted PR 4.9, 95%CI1.53-16.1, p 0.01). The association was not affected bybreast cancer subtype, histological grading, lymphovascular invasion, and tumor-infiltrating lymphocytes level. Conclusions: The NLRvalue was found to be an independent factor for distant metastasis in breast cancer. Its added value on diverse NLR clinical prognostication utility warrants further prospective investigation. Keywords: Neutrophil to lymphocyte ratio, Neoplasm metastasis, Breast neoplasms, Biomarkers.